Association of ICAM3 Genetic Variant with Severe Acute Respiratory Syndrome - Chan, Kelvin Y. K. (J Infect Dis, 2007)
Genetic polymorphisms have been demonstrated to be associated with vulnerability to human infection. ICAM3, an intercellular adhesion molecule important for T cell activation, and FCER2 (CD23), an immune response gene, both located on chromosome 19p13.3 were investigated for host genetic susceptibility and association with clinical outcome. A case-control study based on 817 patients with confirmed severe acute respiratory syndrome (SARS), 307 health care worker control subjects, 290 outpatient control subjects, and 309 household control subjects unaffected by SARS from Hong Kong was conducted to test for genetic association. No significant association to susceptibility to SARS-CoV infection was found for the FCER2 and the ICAM3 single nucleotide polymorphisms. However, patients with SARS homozygous for ICAM3 Gly143 showed significant association with higher lactate dehydrogenase levels (P=.0067; odds ratio [OR], 4.31 [95% confidence interval [CI], 1.37–13.56]) and lower total white blood cell counts (P=.022; OR, 0.30 [95% CI, 0.10–0.89]) on admission. These findings support the role of ICAM3 in the immunopathogenesis of SARS.